PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN GOOGLE CLASSROOM PADA MATERI GAYA DI SMP NEGERI 1 BANYUKE HULU KABUPATEN LANDAK KELAS VIIIC TAHUN PELAJARAN 2022/2023 - alot, oktavianus (JURNAL PENDIDIKAN SAINS DAN APLIKASINYA, 2023)
The development of learning media on style material using Google Classroom media aims to determine feasibility based on the assessment of material experts, media experts and to determine the feasibility of student responses to their users. This study uses the development of learning media using google classroom which includes research and development methods commonly called research and development (R&D) Thiagarajan 3D (Define, Design, Develop). This researcher tested the feasibility of google classroom media style material by 2 material expert validators and 2 media expert validators. In addition, this study also looked at student responses from 30 students of SMP Negeri 1 Bnayuke Hulu towards the use of media that was developed using a questionnaire. Based on the results of the assessment carried out by the material validator expert, it can be concluded that learning media using Google Classroom media style materials obtained an average score of 68% in the appropriate category and the results of the assessment were carried out by media experts with an average score of 71% in the appropriate category. Students' responses to the use of media obtained an average learning score of 79% in the very agree category